Surgery for Primary Hyperparathyroidism in Patients with Preoperatively Negative Sestamibi Scan and Discordant Imaging Studies: The Usefulness of Intraoperative Parathyroid Hormone Monitoring. (January 2013) - Caló, Pietro Giorgio; Pisano, Giuseppe; Loi, Giulia; Medas, Fabio; Tatti, Alberto; Piras, Stefano; Nicolosi, Angelo
The aim of this study was to evaluate the impact of intraoperative parathyroid hormone (PTH) monitoring on surgical strategy, intraoperative findings, and outcome in patients with negative sestamibi scintigraphy and with discordant imaging studies. We divided our 175 patients into 3 groups: group A was methoxyisobutylisonitrile (MIBI)-positive and ultrasonography positive and was concordant (114 patients), group B was MIBI-positive and ultrasonography-negative (50 patients), and group C was MIBI–-and ultrasonography-negative (11 patients). The overall operative success was 99.12% in group A, 98% in group B, and 90.91% in group C, with an incidence of multiglandular disease of 3.5% in group A, 12% in group B, and 9.09% in group C. Intraoperative PTH monitoring changed the operative management in 2.63% of patients in group A and 14% in group B. The use of intraoperative PTH achieves to obtain excellent results in the treatment of primary hyperparathyroidism in high-volume centers, even in the most difficult cases, during MIBI-negative and discordant preoperative imaging studies.